"Living life as if I never had cancer": A study of the meaning of living well in adolescents and young adults who have experienced cancer. Issue 10 (19th July 2020) - Schreiner, Katherine; Grossoehme, Daniel H.; Friebert, Sarah; Baker, Justin N.; Needle, Jennifer; Lyon, Maureen E.
Abstract: Background: Cancer diagnoses pose challenges to adolescents' and young adults' (AYA) physical, mental, and emotional health, and developmental tasks. In order for AYAs, caregivers, clinicians, and other collaborators to optimize health outcomes (coproduction of health), understanding what living well means for AYAs who have experienced cancer is necessary. The objective was to develop an empirical definition of "living well" for AYAs who have experienced cancer to broadly understand AYA values and priorities. This definition may ultimately guide future conversations between caregivers and AYAs, eliciting thorough, personal definitions of living well from individual AYAs. Such conversations may enhance AYA participation in coproducing their health. Procedure: Qualitative analysis using a phenomenological approach of N = 30 structured Respecting Choices interviews conducted with AYAs (14‐21 years; mean 84.2 [SD 69] months postcancer diagnosis with 21% on active treatment) from four tertiary pediatric hospitals in the context of a primary study of a pediatric advance care planning intervention trial. Results: AYAs who have experienced cancer conceptualized "living well" as maintaining physical, mental, and emotional health, as well as engaging in purposeful, age‐appropriate activities with people important to them. Living well had three components: living mindfully, living an identity as a healthy AYA, and spending time with friends and family. Conclusions: Conversations with AYAs who have experienced cancer elicited rich, complex concepts of "living well." Provider initiation of discussions about living well may facilitate personalized goals of care conversations. This study may serve as the basis to design and prototype future clinical interventions to enhance AYA engagement.